Fisherman's village designing a fishing port and fisherfolk community center for Roxas City, Capiz - Morente, Patricia Carina P.; Melgazo, Dylan James L. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Fisherman's Village is a undergraduate thesis proposal in response to the contextual needs of Roxas City, Capiz. It is an architectural response to the agenda of strengthening the identity of the city through empowering the local industry and promoting ecological protection. Fisherman's Village is a redevelopment of the Libas Fishing Port that aims to provide integrated port, administration, and community facilities for empowering the local seafood industry and protecting the fisherfolk community.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Fishing ports -- Roxas City, Capiz; Fishing villages -- Designs and plans. -- Capiz